Bacteria-loaded graphene bioanode for renewable energy generation. (5th March 2023) - Leng, Xuanye; Vazquez, Ricardo J.; McCuskey, Samantha R.; Quek, Glenn; Su, Yude; Nikolaev, Konstantin G.; Costa, Mariana C.F.; Chen, Siyu; Chen, Musen; Yang, Kou; Zhao, Jinpei; Lin, Mo; et al.
Abstract: The high electrical conductivity and low dimensionality of graphene is essential for the development of novel lightweight bioanodes for new-generation energy technologies. However, the integration of graphene in biointerfaces presents a formidable challenge, especially because the surface energy of graphene is not compatible with living matter. Here we propose a sustainable chemical control method to reach the demanded surface hydrophilicity and conductivity of graphene nanowalls to form a lightweight, graphene-based, sponge bioanode. The few-nanometer–thick conductive graphene nanowalls create biocompatible hydrophilic microconfinements to harvest the biomass density of electrogenic Shewanella Oneidensis MR-1. The graphene-based bioanode shows a stable and rapid response with a steady-state biocurrent density of 135.35 mA m −2 realized within a few hours. Our novel and sustainable graphene-based material provides a revolutionary energy opportunity for the establishment of new energy-related graphene industries as well as facilitates many startups. Graphical abstract: A facile and chemical-free method was leveraged to produce the graphene-based bioanode. Balancing the hydrophilicity and conductivity of the graphene nanowalls was achieved by simply tuning its reduction temperature and was the first time, revealed to play an important role in the performance of the microbial electrode. A steady-state bio-current density of 135.35 mA m −2 was realized within a few hours and with long-term duration. Image 1